2018
DOI: 10.1016/j.solener.2018.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor performance monitoring of perovskite solar cell mini-modules: Diurnal performance, observance of reversible degradation and variation with climatic performance

Abstract: The outdoor performance monitoring of two types of perovskite solar cell (PSC) mini-modules based on two different absorbers-CH3NH3PbI3 (MAPI) and Cs0.05FA0.83MA0.17PbI(0.87Br0.13)3 (FMC) is reported. PSC modules displayed markedly different outdoor performance characteristics to other PV technologies owing to the reversible diurnal changes in efficiency, difference in temperature coefficient between absorber layers and response under low light conditions. Examination of diurnal performance parameters on a sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Previously, this approach was pursued to help establish IEC 61215 by correlating outdoor tests results for Si modules with results obtained from various acceleration tests [69][70][71] . To date, studies of PSC outdoor stability are scarce [72][73][74][75] , but the community has gained some critical insights with ISOS-O experiments, such as the importance of light-dark cycling 74 and the unexpectedly high opencircuit voltage at low illumination intensities 73 .…”
Section: Existing Isos Stability Protocolsmentioning
confidence: 99%
“…Previously, this approach was pursued to help establish IEC 61215 by correlating outdoor tests results for Si modules with results obtained from various acceleration tests [69][70][71] . To date, studies of PSC outdoor stability are scarce [72][73][74][75] , but the community has gained some critical insights with ISOS-O experiments, such as the importance of light-dark cycling 74 and the unexpectedly high opencircuit voltage at low illumination intensities 73 .…”
Section: Existing Isos Stability Protocolsmentioning
confidence: 99%
“…Despite this promise, many challenges remain before commercialisation can become a reality: Issues such as current-voltage scan hysteresis call into question the validity of reported efficiencies 5 and stability must be further improved. [6][7][8] One significant route to improving both performance and stability, in particular, is cation substitution within the perovskite crystal structure. The perovskite methylammonium lead triiodide (CH3NH3PbI3 or MAPbI3) has historically been a popular choice of absorber material owing to its ease of processing and phase stability at room temperature.…”
mentioning
confidence: 99%
“…The researchers have also examined the temperature coefficient of their solar cells. While previous reports in perovskite solar cells have shown that this coefficient can be positive or negative depending on the chemical composition of the perovskite absorber layer[8], the researchers have found that the device efficiency does not increase or decrease monotonically with temperature for their multi-cation double-halide perovskite solar cells, illustrating a lack of clear trend for these record-efficiency and long-term stable devices(Figure 1b). Measuring low light behaviour is also important in order to predict energy yield from perovskite modules as this is a more common lighting condition than STC in many of the world's populous locations.…”
mentioning
confidence: 77%
“…New analyses studies the yearly changes in the energy yield of perovskite solar cells under simulated real temperature and irradiance conditions. behaviour which were not taken into consideration in indoor testing [7][8]. In this respect,…”
Section: Ready Cells For Large Scale Systemsmentioning
confidence: 99%